New approaches to the therapy of infectious mononucleosis - Yu. G. Pritulina; V. V. Kunina; A. A. Monastyrsky; T. N. Malyutkina; V. V. Malinovskaya; A. N. Shuvalov (Лечащий Врач, 2021)
Infectious mononucleosis is a viral, widely-spread disease characterized by systemacy of the lesion, with involvement of lymphoid organs and tissues, cardiovascular and immune systems, marrow, liver, spleen and other organs in the pathological process. Comparative study of clinical and laboratory indices in the acute period of infectious mononucleosis was conducted, including treatment with human recombinant interferon alpha-2b, along with highly active antioxidants — C and E vitamins.